Alternative Conceptions of Children about Food - Kumari, Preeti; Upadhyay, Shivani (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
The main objective of the study was to know about children’s alternative conception about food, its need and its function, components of food, concept of balanced diet and the concept of getting energy from food. The purpose of this investigation was to understand logics and reasoning children apply to explain their ideas; so as to discover whether there is any relation between the way children’s conception develop and the way historically scientific ideas evolved. 30 children of 8 to 10 years of age were given different tasks including several possible alternative conceptions about food such as activities based on food, discussion among groups, questionnaire. Qualitative analysis of the data revealed alternative conceptions children hold about food. Data from the study bring out that holding of alternative conception of children related to food is widespread. Children hold several alternative conceptions such as: from all types of food they get energy, food is something that is eaten only, consumption of anything even water would lead to weight gain, proteins are most essential nutrient for the body, animals need food but not nutrients and vitamins, plants do not need food because they can’t eat. Children also have several conceptions that are incomplete or they don’t know the reason behind them such as ‘vitamin pills’ are good for body but don’t know why. It was analyzed that many concepts held by children show resemblance with those held by scientists in the past which show that children base their conceptions on some logics and reasoning. Implication of the study can be that the teachers should give space to children’s alternative conceptions in the class and try to build upon it through hands on activities and visual aids.